INGLIZ VA O‘ZBEK HISSIYOT LEKSIKASINING LINGVOKULTUROLOGIK TAHLILI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article presents a comparative analysis of the linguistic and cultural phenomena of the emotional vocabulary of the Uzbek and English languages, phraseological units, lexical units expressing emotions in English and Uzbek. Their national and cultural peculiarities are revealed and highlighted on the basis of mutual comparative analysis.